Phalerin, a new benzophenoic glucoside isolated from the methanolic extract of Mahkota Dewa [Phaleria macrocarpa (scheff). Boerl.] leaves - Hartati W, Mae Sri; Mubarika, Sofia; Gandjar, Ibnu G; Hamann, Mark T; Rao, KV; Wahyuono, Subagus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Mahkota Dewa [Phaleria macrocarpa (Scheff). Boerl.] is used traditionally to treat cancers in Indonesia. Extract methanol of the leaves displayed a small LC50 value (63.16 Î¼g/ml) on BST (Brine Shrimp Lethality test) assay; therefore a phytochemical study of this extract was undertaken. A new benzophenoic glucoside was isolated from the methanol extract and identified as 4,5-dihydroxy,4â-methoxybenzophenone-3-0-Î²-D-glucoside (Phalerin) based on its spectroscopic data. Phalerin was cytotoxic to myeloma cell line (NS-1) (in vitro) having IC50 of 83 Î¼g/ml or 1.9 x 10-1 mM.Key words: Phaleria macrocarpa, Phalerin, myeloma